Analisis Literasi Keuangan dan Penggunaan Financial Technology (Fintech) Pada Warga KB Bustanul Athfal - Hayati, Neng Ela; Puspita, Vina Anggilia (STMIK Dharmapala Riau, 2025)
This study aims to analyze the level of financial literacy and the use of financial technology (fintech) among residents of KB Bustanul Athfal, a PAUD institution located in Bandung Regency. In the digital era, fintech is am important solution in supporting economic activities, but there is stil a gap in understanding digital financial services, especially among teachers and parents of students. With a qualitative descriptive approach, this study reveals that financial literacy among residents of KB Bustanul Athfal is still low, which has implications for the use of fintech that is not optimal. This study confirms that the level of financial literacy plays an important role in increasing the use of fintech, individuals with good financial understanding tend to be more active and wise in using digital financial services. Systematic educational intervention is needed so that financial technology can be used wisely and support family welfare.